Loss of appetite in amyotrophic lateral sclerosis is associated with weight loss and decreased calorie consumption independent of dysphagia. Issue 2 (18th November 2019) - Mezoian, Taylor; Belt, Emily; Garry, Jamie; Hubbard, Jane; Breen, Christopher T.; Miller, Leah; Levine‐Weinberg, Mark; Nalipinski, Paige; Sullivan, Stacey; Chan, James; Wills, Anne‐Marie
Abstract: Background: Loss of appetite has been reported to affect up to half of people with amyotrophic lateral sclerosis (ALS) and to be associated with weight loss. We wished to test whether loss of appetite correlates with reduced dietary intake independent of dysphagia. Methods: Appetite was measured repeatedly using the Council on Nutrition Appetite Questionnaire (CNAQ) in participants in the Electronic health Application To Measure Outcomes REmotely study. Dietary intake and weight were compared to appetite, ALS Functional Rating Scale‐Revised total and bulbar scores (dysphagia). Results: The average baseline CNAQ score was 30.4 (n = 61; SD = 3.9) with 18.0% scoring <28 points (severe loss of appetite). Lower CNAQ scores correlated with greater weight loss since diagnosis (Pearson correlation coefficient, r = ‐0.34; P = 0.009) and lower baseline energy intake ( P = 0.007), independent of dysphagia. Conclusions: Our results support an association between loss of appetite and decreased calorie intake and weight in ALS which is independent of dysphagia.